Part I: epidemiology and risk factors for stress fractures in female athletes. Issue 1 (2nd January 2020) - Abbott, Alexandra; Bird, Mackenzie L.; Wild, Emily; Brown, Symone M.; Stewart, Greg; Mulcahey, Mary K.
ABSTRACT: Objectives : Stress fractures (SFx) are a common athletic injury, occurring in up to 40% of athletes at some point in their career. These injuries can cause pain, permanent disability, financial burden, and loss of playing time. This review presents updated epidemiology and comprehensive analysis of risk factors for stress fractures, especially as it pertains to female athletes. Results : Stress fractures (SFx) account for up to 10% of all orthopedic injuries and up to 20% of injuries seen in sports medicine clinics, with an incidence among female athletes as high as 13%. Lower extremity SFx represent 80–95% of SFx, and the increased popularity of endurance running has contributed to the tibia (49% prevalence) replacing the metatarsals (9%) as the most common location for lower extremity SFx. Studies have demonstrated that 50% of peak bone mass is acquired during adolescence, a 'peak time' for eating disorder and female athlete triad development; furthermore, catch-up growth cannot be expected in athletes with diminished bone growth in this critical period. The female athlete triad (low energy availability with or without disordered eating, menstrual dysfunction, and low bone mineral density) are well-known risk factors for SFx; the risk of SFx for female athletes presenting with a single aspect of the triad is 15–20%, and this risk increases to 30–50% for female athletes presenting with multiple aspects of the triad. Conclusion : This review provides a basis for how to identify populations at greatest risk for SFx. Prompt recognition of the intrinsic and extrinsic risk factors for SFx in female athletes is imperative to early diagnosis and to develop targeted strategies to prevent SFx occurrence or recurrence.